2017
DOI: 10.7704/kjhugr.2017.17.4.195
|View full text |Cite
|
Sign up to set email alerts
|

National Survey Assessing Treatment ofHelicobacter pyloriInfection in Korean Children: A Pilot Study

Abstract: Background/Aims: The standard guideline for the management Helicobacter pylori infection in Korean children is not present until now. In present study, we conducted the questionnaire survey to investigate the real situation of H. pylori eradication in children. Materials and Methods: Questionnaire concerning the indications of H. pylori eradication, the first choice of treatment modality, the decision method of eradication result, experience of eradication failure, the second choice of treatment modality was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…A national survey on the state of H. pylori eradication therapy in children among doctors who were members of the Korean Society for Pediatric Gastroenterology, Hepatology, and Nutrition in 2016 revealed that the most commonly used first-line eradication therapies were PPI-CLA-based triple therapy (75%) and BIS-based quadruple (AMO) therapy (25%). Most pediatric gastroenterologists had experienced treatment failures, and they frequently chose sequential therapy for rescue therapy [28]. Treatment regimens or eradication rates were not different from those of previous studies.…”
Section: Pediatric H Pylori Eradication Therapy In Koreamentioning
confidence: 99%
“…A national survey on the state of H. pylori eradication therapy in children among doctors who were members of the Korean Society for Pediatric Gastroenterology, Hepatology, and Nutrition in 2016 revealed that the most commonly used first-line eradication therapies were PPI-CLA-based triple therapy (75%) and BIS-based quadruple (AMO) therapy (25%). Most pediatric gastroenterologists had experienced treatment failures, and they frequently chose sequential therapy for rescue therapy [28]. Treatment regimens or eradication rates were not different from those of previous studies.…”
Section: Pediatric H Pylori Eradication Therapy In Koreamentioning
confidence: 99%
“…5 10 복통이나 위장관 출혈 등으로 병원에 오는 소아청소년에게 내시경을 시행하면 H. pylori 감염이 확 인되는 경우를 임상에서 흔히 만나게 된다. 소아청소년에서 H. pylori 감염이 확인되면 제균 치료를 해야 하는지, 한다면 어떤 제균 치료를 해야 할지 의사로서 고민을 할 수 있다.…”
unclassified